STRATEGI SOSIALISASI KOMISI PEMILIHAN UMUM DALAM MENINGKATKAN PARTISIPASI PEMILIH PADA PEMILIHAN WALIKOTA DAN WAKIL WALIKOTA PAYAKUMBUH TAHUN 2017 - Indra, Deky Syukma; Miko, Alfan; Asmawi, Asmawi (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
Payakumbuh City General Election Commission (KPU) succeeded in increasing the voter participation rate in the Payakumbuh Mayor and Deputy Mayor election in 2017 by 4%. Socialization is one aspect of the Payakumbuh City KPU in increasing voter participation. This study discusses the socialization strategy of Payakumbuh City KPU in increasing voter participation in the election of Mayor and Deputy Mayor of Payakumbuh in 2017. The type of research is descriptive with a qualitative approach. The results showed that the strengthening strategy was more dominantly carried out by the Payakumbuh City KPU by strengthening relations between election organizers at each level. However, the Payakumbuh City KPU is not maximal in the implementation of a strategy of confrontation with voters, which only emphasizes the apathetic community and tends to be indifferent to the election process.